The effects of mist irrigation on biological and productive behaviour of globe artichoke - Mauro R.; Di Nicola M.; Longo A.M.G.; Mauromicale G. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
Globe artichoke [Cynara cardunculus L. var. scolymus (L.) Fiori] is an important Mediterranean crop, producing edible immature inflorescences (heads or capitula). In Southern Italy, it plays a pivotal economic role, given its early ripening and potential to provide employment almost all the year-round. However, the critical summer conditions experienced by plantlets, often negatively affect crop establishment, yield and earliness. The goal of our study was to evaluate the opportunity to mitigate these drawbacks by means of mist irrigation, on three early-producing artichoke cultivars (Spinoso di Palermo, Tema 2000 and Violet de Provence). Mist irrigation reduced the maximum air temperature and increased the maximum R.H. within the crop. Such modifications had positive effects on crop establishment and yield, while reducing the production of unmarketable heads at the same time. This was positively reflected on final yield per unit area. Significant genotype x mist irrigation interactions were observed.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)